Program improvement kendali mutu dan kendali biaya pada pasien paliatif oleh kepala ruangan - Yuvensius Pili; Roro Tutik Sri Hariyati; Hening Pujasari; Cori Tri Suryani (Holistik Jurnal Kesehatan, 2024)
Background: Transformation in healthcare in this digital era demands efficiency, hospitals must be able to balance between quality of service and operational costs. The healthcare sector is prone to inefficiencies such as unnecessary care, waste in healthcare, undesirable variations in clinical practice, administrative burden, fraud and abuse.  Purpose: To explore the improvement program of quality control and cost control in palliative patients by the head of the room. Method: This mini research is in accordance with the process of data collection and literature study using questionnaires, observations, interviews, and document studies. Data were analyzed using the POSAC and SWOT (strengths, weaknesses, opportunities, and threats) management approaches. Results: The analysis show that there are problems of high cost, high volume and high risk in palliative patients so that it is necessary to improve the role and function of the head of the room in implementing quality control and cost control. Implementation of solutions in the form of preparation of nurse responsibility guidelines and monitoring checklists by the head of the room in quality control and cost control. Conclusion: The role of the head of the room in managing quality control and cost control in palliative patients is vital. Although there are still various challenges that hinder the optimization of services such as not yet compiled. Suggestion: Development of quality control and cost control guidelines in accordance with the needs of hospitals with a broader scope, Increasing awareness and compliance of professional caregivers to standard operating procedures in health services and services, Conducting socialization of guidelines, SOPs, checklists and tariff patterns so that all professional caregivers are exposed and have the same understanding of quality control and cost control and Quality control and cost control programs need to be used as a curriculum in health institution education and new employee orientation in hospitals.   Keywords: Improvement Program; Quality Control and Cost Control; Role of the Head of the Room.   Pendahuluan: Transformasi di bidang kesehatan era digital ini menuntut adanya efisiensi, rumah sakit harus mampu menyeimbangkan antara kualitas pelayanan dan biaya operasional. Sektor layanan kesehatan rentan terhadap inefisiensi seperti perawatan yang tidak perlu, pemborosan dalam layanan kesehatan, variasi praktik klinis yang tidak diinginkan, beban administrasi, fraud, dan penyalahgunaan.  Tujuan: Untuk mengeksplorasi program improvement kendali mutu dan kendali biaya pada pasien paliatif oleh kepala ruangan. Metode: Penelitian mini projek sesuai dengan literatur dan proses pengumpulan data menggunakan kuesioner, observasi, wawancara serta studi dokumen. Data dianalisis dengan pendekatan manajemen POSAC dan SWOT (strengths/kekuatan, weaknesses/kelemahan, opportunities/peluang, dan rhreats/ancaman). Hasil: Ditemukan masalah high cost, high volume, dan high risk pada pasien paliatif, sehingga perlu dilakukan program improvement peran dan fungsi kepala ruangan dalam pelaksanaan kendali mutu dan kendali biaya. Implementasi solusi berupa penyusunan panduan tanggung jawab perawat dan cheklist monitoring oleh kepala ruangan dalam kendali mutu dan kendali biaya. Simpulan: Peran kepala ruangan dalam pengelolaan kendali mutu dan kendali biaya pada pasien paliatif sangat vital. Meskipun masih terdapat berbagai tantangan yang menghambat optimalisasi layanan, seperti belum tersusunnya panduan dan standar operasional prosedur, serta kesulitan dalam pengelolaan sumber daya. Saran: Pengembangan panduan kendali mutu dan kendali biaya sesuai dengan kebutuhan rumah sakit dengan scope yang lebih luas. Peningkatan awareness dan kepatuhan profesional pemberi asuhan terhadap standar operasional prosedur dalam layanan dan pelayanan kesehatan. Melakukan sosialisasi panduan, SOP, checklist, dan pola tarif agar semua profesional pemberi asuhan terpapar dan memiliki pemahaman yang sama dalam kendali mutu serta kendali biaya. Hal ini perlu dijadikan kurikulum dalam pendidikan institusi kesehatan dan orientasi pegawai baru di rumah sakit.   Kata Kunci: Kendali Mutu dan Kendali Biaya; Peran Kepala Ruangan; Program Improvement.